Analisis Flypaper Effect Pada Pengaruh PAD, DAU, dan DAK Terhadap Belanja Daerah di Nusa Tenggara Timur - Solicha, Firda Armaatus; Hanifa, Nurul (Jurnal Ekonomika : INDEPENDEN, 2024)
The flypaper effect arises when regions depend on funds from the center to support regional expenditures. This dependence raises concerns regarding the implementation of increasing regional autonomy. This study analyzes the flypaper effect related to the influence of PAD, DAU, and DAK on East Nusa Tenggara regional spending in 2017-2023. By using a quantitative approach and panel data regression techniques, the results obtained are PAD and DAU have a significant effect on regional spending, while DAK has no effect. The PAD coefficient has a more significant effect than DAU and DAK, indicating the absence of flypaper effect in East Nusa Tenggara Province. Keywords : Regional Original Revenue, General Allocation Fund, Special Allocation Fund, Regional Expenditure, and Flypaper effect